Novel methods to induce complex coacervation using dual fluid nozzle and metal membranes: Part I – Use of metal membranes for emulsification - Ferreira, Sungil [UNESP]; Nicoletti, Vania Regina [UNESP]; Dragosavac, Marijana (Elsevier, 2022)
This study is part I of two parts where the use of metal membranes was evaluated to produce emulsions and to induce complex coacervation. In this work, we aimed to produce emulsion droplets using metal membranes to be used in complex coacervation in batch stirring and by a new method in which coacervation is induced using a two-fluid nozzle. Investigation on the optimum membrane morphology, dispersed phase injection rate and emulsification shear stress was carried out. Emulsions of gelatin and ginger oil (4% and 10% w/w) were produced by membrane emulsification in a dispersion cell, with droplet sizes varying from 32 to 128 µm; gelatin concentration had great influence on droplet size and size distribution. Complex coacervation between gelatin and gum Arabic without the use of crosslinking agents was carried out by atomization and batch stirring, and the size of the parent emulsion droplets, coacervation shear stress and emulsion formulation influenced the size of the capsules produced, which varied from 35 to 151 µm. Batch stirring complex coacervation produced single core capsules and atomization coacervation produced multicore capsules, both with spherical morphology. Encapsulation yield of dried capsules varied from 37% to 99% and encapsulation efficiency 5–66%. Formulation had a greater effect on the encapsulation efficiency than on the encapsulation yield.
Keywords: Dimensionless numbers; Dispersion cell; Low shear emulsification; Membrane morphology; Particle size distribution